1982
DOI: 10.2307/3281100
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathogenicity of Naegleria fowleri and Naegleria gruberi for Established Mammalian Cell Cultures

Abstract: Amebae of Naegleria fowleri and Naegleria gruberi were cytopathic for nine established mammalian cell cultures, including mouse and human fibroblasts, rabbit and monkey kidney cells, rat and mouse neuroblastoma cells, baby hamster kidney cells, and human epithelioma and carcinoma cells. Nine strains of N. fowleri were equally cytopathic for rodent neuroblastoma cells. As few as one ameba per million neuroblastoma cells destroyed the mammalian target cells after 9 days. The N. fowleri grew and destroyed rat neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
41
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 16 publications
3
41
0
Order By: Relevance
“…Cytopathogenicity of N. fowleri in mammalian cell cultures has been studied since 1982 (Marciano-Cabral et al 1982). The formation of CPE on cell monolayers depends on susceptibility of the monolayer type.…”
Section: Resultsmentioning
confidence: 99%
“…Cytopathogenicity of N. fowleri in mammalian cell cultures has been studied since 1982 (Marciano-Cabral et al 1982). The formation of CPE on cell monolayers depends on susceptibility of the monolayer type.…”
Section: Resultsmentioning
confidence: 99%
“…The ability to elicit cytopathic effects on cells in culture does not appear to define pathogenicity for Naegleria. That is, while species of Naegleria such as N. lovaniensis and Naegleria gruberi destroy mammalian cells in vitro (Marciano-Cabral et al, 1982;Marciano-Cabral & Fulford, 1986), they have yet to be shown to be causative of human disease. Also, the ability to tolerate temperatures of 37 u C or higher does not appear to be a defining marker of pathogenicity for Naegleria.…”
mentioning
confidence: 99%
“…It is, therefore, intimately involved in pathogenesis (12). The process has been named trogocytosis, the piecemeal engulfment of mouse embryo cells by N. fowleri (12). It is now known that trogocytosis is accomplished by amoebastomes (2), which amoebae use to engulf particles of various sizes, including cultivated mammalian cells.…”
mentioning
confidence: 99%
“…Phagocytosis is a basic function of this amoeba and one that causes the destruction of cells, whether in cell culture or in human tissue. It is, therefore, intimately involved in pathogenesis (12). The process has been named trogocytosis, the piecemeal engulfment of mouse embryo cells by N. fowleri (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation